BIOLOGICAL USE OF OZEMPIC AND ITS EFFECTS: A NARRATIVE REVIEW OF THE LITERATURE (International Seven Journal of Multidisciplinary, 2024)
Objective: To analyze the biological use of Ozempic and its effects. Literature Review: Obesity is the global pandemic of the twenty-first century, it is a chronic pathology, characterized essentially by the accumulation of excess body fat. In this regard, it is necessary to highlight Ozempic, a drug prescribed for the treatment of type 2 diabetes contains the active substance "semaglutide", which helps reduce blood sugar levels. Despite this, this has been a product widely consumed by individuals who want to lose their weight in a miraculous way and without the monitoring of a qualified health professional (GOMES; TREVISAN, 2021). Final considerations: It should be noted that the irrational use of these drugs can cause harm to consumers, from mild damage to serious damage, which can lead to death. Since there are people who use these drugs without clinical indication and who do not understand the action and effects they cause in the body, they often care only about weight loss in search of aesthetic standards, thus leaving health in the background.